Profil Pembelajaran IPA di SMP Inklusi ; Analisis Kebutuhan Media Pembelajaran Digital - Nabila Trisna Shafira (IKIP Siliwangi, 2022)
Abstrack The science learning process in inclusive schools requires learning media that accommodates the various advantages and limitations of students. So far, the development of digital learning media for science learning has not considered the needs of inclusive students. This study aims to describe the profile of science learning in inclusive junior high schools in order to analyze the needs of digital learning media. The research method uses descriptive methods with quantitative and qualitative approaches. The research instrument is an interview sheet with biology teachers and GPK (Special Advisory Teachers) at SMPN 34 Padang and a survey questionnaire sheet on the use of digital learning media on 30 students of class VII. The results of this study revealed that more than 63% of students felt bored and less interested in using the available teaching materials. This is due to the absence of variations in learning media. Students need diverse and interesting learning media. As many as 76% of students have never used digital teaching materials and around 73% agreed to use digital learning media in the learning process. The results of interviews with GPK (Special Advisory Teachers) are known that more concrete learning media is needed and accommodates the needs of students with special needs. Keywords : Science Learning, Inclusive Junior High School, Digital Learning MediaAbstrak Proses pembelajaran IPA di sekolah inklusi membutuhkan media pembelajaran yang mengakomodasi berbagai keunggulan dan keterbatasan peserta didik. Sejauh ini pengembangan media pembelajaran digital untuk pembelajaran IPA belum mempertimbangkan kebutuhan peserta didik inklusi. Penelitian ini bertujuan memaparkan profil pembelajaran IPA di SMP inklusi dalam rangka analisis kebutuhan media pembelajaran digital. Metode penelitian menggunakan metode deskriptif dengan pendekatan kuantitatif dan kualitatif. Intrumen penelitian berupa lembar wawancara dengan guru biologi dan GPK(Guru Pembimbing Khusus) SMPN 34 Padang dan lembar angket survey penggunaan media pembelajaran digital pada 30 orang peserta didik kelas VII. Hasil dari penelitian ini terungkap bahwa lebih dari 63% peserta didik merasa bosan dan kurang termotivasi menggunakan bahan ajar yang tersedia. Hal ini disebabkan oleh tidak adanya variasi media pembelajaran. Peserta didik membutuhkan media pembelajaran yang beragam dan manarik. Sebanyak 76% peserta didik belum pernah menggunakan bahan ajar digital dan sekitar 73% menyetujui penggunaan media pembelajaran digital dalam proses pembelajaran. Hasil wawancara dengan GPK(Guru Pembimbing Khusus) diketahui dibutuhkan media pembelajaran yang lebih konkrit dan mengakomodasi keperluan peserta didik berkebutuhan khusus.Kata Kunci: Pembelajaran IPA, SMP Inklusi, Media Pembelajaran Digital